"I Didn't Know She Took Pictures": African American Women Photographers in the Long Civil Rights Movement - Brady, Emily Rose (2021)
This thesis provides a meaningful intervention in the history of African American women photographers in the long Civil Rights Movement. These women were “agents of change,” who cultivated “spaces of agency” in their lives and in their images. This highlights the importance of everyday activism within the movement; through acts of spatio-symbolic reclamation, these women were able to both occupy space as photographers and document the community-orientated activism around them. The photographers, and their photography, claimed both physical space and symbolic space in the long Civil Rights Movement. As photographers, they occupied physical space by creating “spaces of agency” wherein they empowered people in their communities to have their photographs taken, and the photographers symbolically claimed space in the photographic canon of the Civil Rights Movement as artists and businesswomen. With their photography, they also operated within physical and symbolic “spaces of agency”: physically their photographs occupied space – as the images were displayed in homes or in publications – and symbolically their work documented acts of spatio-symbolic reclamation, as African Americans challenged segregation by occupying and integrating public space. As such, this thesis intervenes in scholarship of both the long Civil Rights Movement and the spatial turn, whilst centring the activism and agency of African American women. Navigating the often conflicting societal pressures of the politics of respectability, these women worked within a long Civil Rights Movement to achieve a literal and metaphorical reclamation of space through their photography.